2021
DOI: 10.12928/telkomnika.v19i2.18148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of humidity on sand and dust storm attenuation predictions based on 14 GHz measurement

Abstract: Several models were proposed to predict the attenuation of microwave signals due to sand and dust storms. Those models were developed based on theoretical assumptions like Rayleigh approximation, Mie equations or numerical methods. This paper presents a comparison between attenuation predicted by three different theoretical models with measured attenuation at 14 GHz. Dielectric constant of dust particles is one of the important parameter in prediction models. This constant is estimated from measured dust sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This is because finer particles have more surface area, leading to more absorbed water and less free water, resulting in a lower dielectric constant. Some researchers found that millimeter waves are deflected more by dry clayey particles than by dry sandy particles [75]. It is also observed that after absorbing moisture, millimeter waves are more negatively affected by sand particles in humid climates.…”
Section: ) Effect Of Humidity On Dielectric Constantmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because finer particles have more surface area, leading to more absorbed water and less free water, resulting in a lower dielectric constant. Some researchers found that millimeter waves are deflected more by dry clayey particles than by dry sandy particles [75]. It is also observed that after absorbing moisture, millimeter waves are more negatively affected by sand particles in humid climates.…”
Section: ) Effect Of Humidity On Dielectric Constantmentioning
confidence: 99%
“…The results of indirect attenuation measurements from studies [129], [208], [209], [210], [211], [212], [214], [200], [149], [137], and [75] are also plotted in Fig. 14…”
Section: A Measurements At Mw and MM Wave Frequenciesmentioning
confidence: 99%
“…Humidity was observed to be higher during the dust storm events. Available conversion model is used to incorporate the effect the humidity in the dielectric constant [7]. The predicted attenuation using humid dielectric constant has been found to be much higher than the predicted attenuation using dry dust condition [7].…”
Section: Introductionmentioning
confidence: 98%
“…Available conversion model is used to incorporate the effect the humidity in the dielectric constant [7]. The predicted attenuation using humid dielectric constant has been found to be much higher than the predicted attenuation using dry dust condition [7]. Wind turbulence during storms also affects the orientation angle of falling sand and dust particles that describes the orientation of a particle's axis of symmetry (or revolution).…”
Section: Introductionmentioning
confidence: 99%
“…High-frequency bands, such as a super-high carrier frequency band (S-band), 3 GHz to 30 GHz, and an extremely high carrier frequency band (E-band), 30 GHz to 300 GHz, are going to be used to be able to fulfill the high data rates demand in the network. Rising frequencies may cause issues to the wireless signals, such as scattering, depolarization, and phase noise [2]- [5].…”
Section: Introductionmentioning
confidence: 99%